Pengaruh Bantuan Proram Keluara Harapan Dan Bantuan Pangan Non Tunai Terhadap Kesejahteraan Masyarakat Di Kelurahan Toloa Kecamatan Tidore Selatan - Yakub, Putriyani; Dahlan, Fadli; Majojo, Muhammad Yasin (Peneliti.net, 2025)
This study aims to analyze the influence of the Family Hope Program (PKH) and Non-Cash Food Assistance (BPNT) on Community Welfare in Toloa Village, South Tidore District, Tidore Islands City. This study uses a quantitative approach. The sampling method used is a census or population study, involving the entire population that meets the criteria (still receiving assistance) of 70 Family Cards (KK). The results of the study indicate that: (1) The Family Hope Program (PKH) variable partially has a positive and significant effect on community welfare, as evidenced by the t-count value of 3.429 > t-table 1.965 and a significance value of 0.001 < 0.05. (2) The Non-Cash Food Assistance (BPNT) variable partially has a positive and significant effect on community welfare, with a t-count value of 3.318 > t-table 1.965 and a significance value of 0.001 < 0.05. (3) Simultaneously, the PKH and BPNT variables have a positive and significant effect on community welfare, as indicated by the F-count value of 7.991 > 3.132 and a significance value of 0.001 < 0.05. From this research, the PKH and BPNT social assistance programs, both partially and simultaneously, have been proven to have a positive and significant impact in improving community welfare in Toloa Village, South Tidore District.